Do non-technological innovations and CSR matter for environmental innovation? An empirical analysis of a sample of innovators. (2017) - Bas, Christian Le; Poussing, Nicolas
This paper aims to fill a gap in the field of determinants of environmental innovation by investigating whether non-technological innovations and corporate social responsibility matter for environmental innovation. Our empirical analysis studies a sample of innovators from Luxembourg. We draw on the Community Innovation Survey and a corporate social responsibility survey specific to this country. Our econometric exercises show that organisational innovation and marketing innovation are positively and significantly linked to environmental innovation. The result holds when product and process innovations are included as independent variables. Corporate social responsibility plays a role as well.